Epigenetic silencing of ZBTB28 promotes renal cell carcinogenesis. Issue 2 (23rd June 2021) - Tong, Xin; Xu, Lu; Rong, Rong; Su, Xianwei; Xiang, Tingxiu; Peng, Weiyan; Shi, Taoping
Abstract: Aim: Zinc finger and BTB domain‐containing protein 28 ( ZBTB28 ) is a potential tumor suppressor for some cancers. However, its epigenetic regulation and functions in renal cell carcinoma (RCC) remain to be elucidated. Methods: The expression of ZBTB28 mRNA was analyzed by semi‐quantitative reverse transcription polymerase chain reaction (PCR) in nine RCC cell lines and normal kidney tissues. Methylation status of ZBTB28 promoter was assessed by methylation‐specific PCR in RCC cell lines, primary RCC, tumors and adjacent tissues. The involvement of ZBTB28 in cell proliferation and migration was investigated. Results: ZBTB28 promoter was hypermethylated in 88.9% (8/9) of RCC cell lines with reduced ZBTB28 mRNA expression, and could be reversed by DNA methyltransferase inhibitors. The methylation of ZBTB28 promoter was detected in 73.5% (36/49) of primary RCC tissues, compared with 7.1% (1/14) in normal tissues. Overexpression of ZBTB28 significantly inhibited RCC cell proliferation and migration, and induced apoptosis. Further analyses revealed that ZBTB28 upregulation could inhibit multiple oncogenic signaling transduction pathways. Conclusion: ZBTB28 is frequently silenced by promoter methylation in RCC pathogenesis and functions as a novel tumor suppressive gene. ZBTB28 may be a potential target for the development of RCC therapeutic strategies. Abstract : ZBTB28 is frequently silenced by promoter CpG methylation in RCC cell lines. (a) ZBTB28 transcript detected in human normal adult tissues using semiquantitative reverse transcription PCR. (b) ZBTB28 is frequently silenced and methylated in RCC cell lines. M, methylated; U, unmethylated. (c) Pharmacologic demethylation reactivates ZBTB28 expression using 5‐aza‐2‐deoxycytidine alone or in combination with trichostatin A (A+T). (d) Schematic strsucture of the ZBTB28 CpG island. Exon 2 (indicated with a black rectangle), CpG sites (short vertical lines), MSP and BGS regions analyzed are indicated. (e) Representative results of BGS analysis of ZBTB28 in RCC cell lines.